Kesesuaian Struktur Organisasi Perangkat Daerah di Pemerintah Kota Pekanbaru Berdasarkan PP No. 41 Tahun 2007 - Ella, Susy (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2009)
In the year of 2007, Indonesian Government issued Peraturan Pemerintah No. 41 Tahun 2007 tentang Organisasi Perangkat Daerah as guidance to re-organize and control government organization in local-government level. As stated in the decree, every local government must obey this rule in order to create effective, efficient, rational, and proportional organization. This study aimed to look at the fitness between organization structure in City of Pekanbaru with Peraturan Pemerintah No. 41 Tahun 2007 using two dimensions. 1) organization size and 2) core business grouping. It applied qualitative descriptive in method. The result was shown that re-organization among local-government organization in Pekanbaru had met the requirement noted in Peraturan Pemerintah No. 41 Tahun 2007.